Women’s empowerment and gender equity in agriculture: A different perspective from Southeast Asia - Akter, Sonia; Rutsaert, Pieter; Luis, Joyce; Htwe, Nyo Me; San, Su Su; Raharjo, Budi; Pustika, Arlyna (Elsevier, 2017)
Women’s empowerment is considered a ‘prerequisite’ to achieving global food security. Gender systems, however, are diverse and complex. The nature and extent of gender inequity and the conditions necessary to empower women vary across countries, communities and regions. The study of different gender systems is thus fundamental to capture cross-cultural variations in gender specific needs and constraints to effectively address gender gaps. Although the status of women in agriculture has received extensive attention in the literature in recent decades, a research gap persists regarding the state of gender inequity in Southeast Asian agriculture. The current paper contributes to the geographical scope of the literature by presenting empirical evidence of gender inequity from four Southeast Asian countries: Myanmar, Thailand, Indonesia and the Philippines. Using the framework recommended by the Women’s Empowerment in Agriculture Index (WEAI), 37 focus group discussions were conducted with 290 women farmers in the above mentioned countries. The results reveal trends that contradict the conventional narratives of gender inequity in agriculture in certain domains of empowerment. In all four countries, women appear to have equal access to productive resources such as land and inputs, and greater control over household income than men. Important intra-regional heterogeneity is observed in terms of community-level empowerment. While women play an active role in agricultural groups in Thailand and in the Philippines, this is predominantly men’s territory in Indonesia and Myanmar. These findings imply that country-specific gender intervention frameworks are necessary to overcome gender gaps in agriculture